The effect of exogenous fibrolytic enzymes and a ferulic acid esterase-producing inoculant on the fibre degradability, chemical composition and conservation characteristics of alfalfa silage - Lynch, J. P.; Jin, L.; Lara, E. C. [UNESP]; Baah, J.; Beauchemin, K. A. (Elsevier B.V., 2014)
The objective of this study was to determine the effect of applying fibrolytic enzymes at ensiling, either alone or in combination with a ferulic acid esterase-producing bacterial silage inoculant, on the silage conservation characteristics and nutritive value of alfalfa (Medicago sativa L). Second-cut alfalfa (340 g DM/kg fresh crop) was harvested, wilted, chopped and sub-sampled into 24 batches. Samples were randomly allocated in triplicate to one of four enzyme product treatments supplying endoglucanases and xylanases: none (control), EN1, EN2, EN3; applied alone or in combination with a ferulic acid esterase-producing silage inoculant (FAEI). Treatments were arranged in a 4 x 2 factorial design. All enzyme treatments were applied at 2 ml enzyme product/kg herbage DM, and inoculant was applied at 1 x 10(5) cfu/g fresh herbage. Samples were packed into laboratory-scale silos and stored for 7, 27 or 70 days, and analysed for dry matter (DM) losses, aerobic stability, chemical composition and in vitro ruminal degradability. The use of enzymes did not affect (P>0.05) ensilage DM losses or lactic or acetic acid concentrations after 70 days of ensilage, compared to the control silage. Silage produced using EN1 had lesser neutral detergent fibre (aNDF, P=0.046) and acid detergent fibre (ADF; P=0.006) concentrations than control silage. However, no difference (P>0.05) was observed between the control silage and silage produced with EN1 for aNDF or ADF degradability (NDFD, ADFD). Silages produced with FAEI had greater DM losses (P=0.017) and pH (P<0.001) and lesser NDFD (P=0.019), ADFD (P=0.010) and proportion of lactic acid in the total fermentation products (P=0.006) after 70 days of ensilage, compared to uninoculated silages. The use of fibrolytic enzymes did not have a major effect on the ensilage fermentation of alfalfa, either ensiled alone or with an inoculant. No advantage in ruminal DM or fibre degradability was observed for silages produced with fibrolytic enzymes. The use of a ferulic acid esterase-producing inoculant alone did not improve the nutritive value of alfalfa silage, and did not promote any incremental effects when applied in combination with fibrolytic enzyme products. Crown Copyright (C) 2014 Published by Elsevier B.V. All rights reserved.
Keywords: Fibrolytic enzyme; Fibre; Alfalfa; Silage; Ferulic acid esterase; Lactobacillus